Peranan etika kerja Islam dalam meningkatkan kualiti perkongsian pengetahuan dalam kalangan kakitangan perpustakaan akademik di Malaysia - Norashikin, Ibrahim (2024)
The topic of the role of Islamic work ethics in improving knowledge sharing among academic library staff in Malaysia is increasingly important in the study of knowledge management and human resources. Based on moral principles and Islamic religious values, this work ethic influences the attitude and behavior of employees, thereby improving the quality of knowledge sharing in the workplace. Academic libraries play an important role in supporting university curriculum and research. In the era of globalization and communication technology, library information demand is increasing, making knowledge sharing critical to organizational performance. However, obstacles include less open individual attitudes, unsupportive organizational culture, and a lack of worker trust. This research examines several factors that influence knowledge-sharing behavior, including personality traits, authentic leadership, information and communication technology, and Islamic work ethics as moderating factors. Integrating Islamic work ethics with sincerity, justice, trustworthiness, and diligence principles can foster a collaborative and integrity-driven work culture. This study uses a quantitative approach through an online survey of academic library staff in Malaysia, involving 176 respondents who were analyzed using SPSS and Partial Least Square (PLS-SEM) SmartPLS software. The findings show a positive relationship between personality traits, authentic leadership, communication and information technology, Islamic work ethics, and knowledge-sharing behavior. Practically, this study provides insights for organizations to increase knowledge-sharing activities by focusing on the Islamic context in Malaysia. In theory, Islamic work ethics increase the positive effects of personality traits and ICT on knowledge sharing by emphasizing honesty, trust, and responsibility. Despite this, this study acknowledges its weaknesses, such as the use of a small sample size and methodological limitations. Further research with larger and more diverse samples and mixed approaches is suggested to deepen understanding across multiple organizational contexts.